In-plane grain boundary induced defect state in hierarchical NiCo-LDH and effect on battery-type charge storage - Ban, Jinjin; Wen, Xiaohan; Lei, Honghong; Cao, Guoqin; Liu, Xinhong; Niu, Chunyao; Shao, Guosheng; Hu, Junhua (Nano research, 2023)
Domain boundaries are regarded as the effective active sites for electrochemical energy storage materials due to defects enrichment therein. However, layered double hydroxides (LDHs) tend to grow into single crystalline nano sheets due to their unique two-dimentional (2D) lattice structure. Previously, much efforts were made on the designing hierarchical structure to provide more exposed electroactive sites as well as accelerate the mass transfer. Herein, we demonstrate a strategy to introduce low angle grain boundary (LAGB) in the flakes of Ni/Co layered double hydroxides (NiCo-LDHs). These defect-rich nano flakes were self-assembled into hydrangea-like spheres that further constructed hollow cage structure. Both the formation of hierarchical structure and grain boundaries are interpreted with the synergistic effect of Ni 2+ /Co 2+ ratio in an “etching-growth” process. The domain boundary defect also results in the preferential formation of oxygen vacancy (Vo). Additionally, density functional theory (DFT) calculation reveals that Co substitution is a critical factor for the formation of adjacent lattice defects, which contributes to the formation of domains boundary. The fabricated battery-type Faradaic NiCo-LDH-2 electrode material exhibits significantly enhanced specific capacitance of 899 C·g −1 at a current density of 1 A·g −1 . NiCo-LDH-2//AC asymmetric capacitor shows a maximum energy density of 101.1 Wh·kg −1 at the power density of 1.5 kW·kg −1 .